URGENSI LEGALITAS LEMBAGA KEUANGAN MIKRO SYARIAH - Dadan Muttaqien (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
Baitul Maal Wat Tamwil (BMT) is a customer self-help groups as an economic institution of the people who seek to develop productive enterprises and investment with the system of profit and loss sharing to enhance the quality of small economies. BMT combines two different activities in nature (profit and nonprofit) in one institution. BMT existence is expected to contribute significantly in developing a real economy sector, especially for business activities which do not meet all the requirements to obtain financing from the Islamic banking institution in general. Currently, BMT has triggered the development of small business better. The existence of BMT is helpful undercapitalized small businesses with financing facilities and financing facilities resulting in increased revenue. Behind this success BMT harbored a matter of emergency to get a solution. Therefore, in this paper, described how the operational BMT and common constraints it faces, and most importantly is the solution to the fore. BMT as Islamic microfinance institutions have had time to improve itself to meet the needs of the community will fund the development of micro-enterprise activities. The presence of BMT is one contribution to the success of the development process, so that slowly but surely to erode or reduce the number of poor in Indonesia.